Effect of pH on the Langmuir monolayers of Zirconyl Stearate and the synthesized Zirconium Oxide thin films - Choudhary, Raveena (My University, 2017)
Zirconium oxide is a very important material from applications point of view finds applications in coatings and as oxygen sensor. The control of thickness, roughness and surface morphology are some of the important parameters which need to be controlled. Langmuir-Blodgett (LB) thin film deposition method is known for the precise control of thin film parameters. In this work the thin uniform films of zirconium oxide were synthesized from the ZrO-stearate LB films. Characteristics of the Langmuir monolayers control the quality of LB films and the morphology of the final oxide thin film. ZrO-stearate Langmuir monolayers were deposited and characterized on the surface of the Langmuir trough. It was observed that at too low pH the ZrO2+ ions do not get incorporated in the monolayer. As the pH of subphase was increased the compaction of the film and its static elasticity in the solid phase was enhanced indicating an increase in ZrO2+ ion incorporation. An important result to emerge from these studies was that for very high pH (8.3) the structure of the films opens up. Analysis of π-A isotherms showed that pH 7.3 monolayer has good parameters for the LB deposition. Cyclic compression and expansion of the monolayer showed that while the Mma reduces steadily, the static elasticity of the solid phase gets cycled. This behavior can be explained on the basis of the behavior of double bonded oxygen attached to the Zr atom. The oscillating barrier characterizations of ZrOstearate monolayers at different frequencies and pH values were recorded. This characterization also confirmed the stability of the monolayers at pH 7.3. The LB films of ZrO-stearate were Z-type. The transparent Zirconium oxide thin films on glass substrate were synthesized by deposition of 9, 14, 20 layers of ZrO-stearate at 7.3 pH followed by drying, removal of stearate chain and calcination. The presence of Zr in the calcined films was checked by EDS. 15 layers deposited at pH 7.3 formed the best film with grain size of about 23 nm. The effect of pH on the final film morphology was determined by depositing 15 layers for 6.3, 7.9 and 8.3 pH values. The TR for the pH 6.3 and 8.3 monolayers was too low so the uniform films could not be deposited. For the pH 7.9 the deposition was possible but the final films have larger grain size and were more granular and uneven at local level.
Keywords: Langmuir Monolayers; LB Films; Stearic Acid; Zirconyl Stearate; Zirconium Oxide